Adjuvant radiotherapy for patients with pathologic node‐negative esophageal carcinoma: A population based propensity matching analysis. Issue 2 (11th December 2019) - Gao, Hui‐Jiang; Shang, Xiao‐Bin; Gong, Lei; Zhang, Hong‐Dian; Ren, Peng; Shi, Guo‐Dong; Wei, Yu‐Cheng; Yu, Zhen‐Tao
Abstract : Background: The impact of adjuvant treatment for esophageal carcinoma with tumor‐negative lymph nodes after upfront radical esophagectomy is still uncertain. This study investigated the effects of postoperative radiotherapy in pT1‐3N0 esophageal carcinoma after radical resection. Method: We retrospectively identified pT1‐3N0M0 esophageal carcinoma patients between 2000 and 2016 from the Surveillance, Epidemiology, and End Results database. Patients with upfront esophagectomy were categorized as having received surgery alone (SA) and surgical resection followed by adjuvant radiotherapy (SA + RT). Propensity score matching, univariate and multivariate analysis were performed to compare overall survival (OS) and cause‐specific survival (CSS). Results: A total of 2862 patients were identified, of whom 274 received SA + RT and 2588 received SA. The median follow‐up was 60.4 months (95%CI, 58.7–62.1 months). The five‐year OS and CSS were better for SA group compared with SA + RT group ( P < 0.001, respectively). Furthermore, after matching, the OS and CSS were still significantly better for SA patients. For T subgroup analysis, postoperative radiotherapy was an independent prognostic factor only for pT1 patients with worse OS, without survival differences for pT2 and pT3 patients. However, after multivariate cox analysis, postoperative radiotherapy can provide significantly better OS for pT3 patients with tumor length ≥5 cm ( P = 0.03; 95%CI, 0.29–0.94). Conclusions: Among pT1‐3N0M0 esophageal carcinoma patients, postoperative radiotherapy can provide significantly better OS for pT3 patients with tumor length ≥5 cm. However, there are no survival benefits for pT1‐2 patients after SA + RT procedure. This finding may have significant implications on the use of adjuvant radiation in patients with pN0 disease.